Consistent Microbial Assembly in the Rhizosphere of Crop Wild Progenitors - Miguel de Celis; María José Fernández‐Alonso; María Leo; Ignacio Belda; Carlos García; Brajesh K. Singh; Yue Yin; Juntao Wang; Juan Gaitán; Luis Abdala‐Roberts; Fernando D. Alfaro; Diego F. Angulo; et al. (Global Ecology and Biogeography, 2026)
Aim Microbiome rewilding seeks to harness plant‐microbe interactions for sustainable agriculture, assuming that ancestral microbial partners have been lost during domestication and geographical spread. Designing microbiome rewilding strategies requires a quantitative and predictive understanding of the fundamental ecological processes—selection, dispersal, and drift—driving microbial assembly and persistence in the rhizosphere of crop wild progenitors (CWPs). Location Global. Time Period Present. Major Taxa Studied Rhizosphere bacteria and fungi. Methods Here, we leveraged a global survey of the CWPs of 10 major crops across their native habitats to assess the roles of selection, dispersal, and drift in shaping rhizosphere microbial communities. We combined compositional and phylogenetic turnover metrics with local network analyses to evaluate community assembly and structure in response to environmental gradients. Results We found host‐driven selection, reflected by low phylogenetic turnover at the whole‐tree level, but also selection driven by differences among individual plants, as indicated by high turnover among closely related taxa. The high level of compositional turnover found suggests dispersal limitations, which in the context of CWPs, may indicate host‐mediated filtering of external microbial taxa. The network structure was constant across CWPs; however, bacterial and fungal structures diverged, pointing to distinct community organisations. Bacterial communities presented higher modularity and lower clustering than fungal communities. Climate, especially seasonal temperature and precipitation, was the main driver of both bacterial and fungal structures. However, host identity best predicted bacterial structure, while NDVI, a proxy for vegetation status, better explained fungal patterns. Main Conclusions Bacterial and fungal communities are shaped by consistent assembly processes across CWPs, but their structures diverge. With the identification of the assembly processes driving microbiome composition in the rhizosphere of CWPs, this work paves the road to incorporate microbiome rewilding in the toolbox of sustainable agriculture.

Forest expansion and irrigated agriculture reinforce low river flows in southern Europe during dry years - Sergio M. Vicente-Serrano; Ahmed El Kenawy; Dhais Peña-Angulo; Jorge Lorenzo-Lacruz; Conor Murphy; Jamie Hannaford; Simon Dadson; Kerstin Stahl; Iván Noguera; Magí Fraquesa; Beatriz Fernández-Duque; Fernando Domínguez-Castro (Journal of Hydrology, 2025)

Framework for scaling-up extraction processes in nutraceutical beverages: A simulation, techno-economic, and environmental analysis approach - Yris Gonzalez; Fernando Zea; Alexander Espinoza; Daniela Galatro; Glenda Pilozo; Wilfredo Angulo; Manuel Rodríguez Hernández; Jesus Urrucsaca; Marcela Muzzio; Michael Rendón-Morán; Patricia Manzano (Food and Bioproducts Processing, 2024)

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

Repellent screening of ethanol extracts from plants of the Yucatan Peninsula against Bemisia tabaci (Gennadius, 1889) and chemical profile of Malpighia glabra L. leaves - Monserrat C. Esquivel-Chi; Esaú Ruiz-Sánchez; Horacio S. Ballina-Gómez; Jesús Martín; Fernando Reyes; Germán Carnevali; Jose L. Tapia-Muñoz; Marcela Gamboa-Angulo (Journal of Plant Diseases and Protection, 2024)

The abundant fraction of soil microbiomes regulates the rhizosphere function in crop wild progenitors - Miguel de Celis; María José Fernández‐Alonso; Ignacio Belda; Carlos García; Raúl Ochoa‐Hueso; Javier Palomino; Brajesh K. Singh; Yue Yin; Jun‐Tao Wang; Luis Abdala‐Roberts; Fernando D. Alfaro; Diego Angulo‐Pérez; et al. (Ecology Letters, 2024)
The rhizosphere influence on the soil microbiome and function of crop wild progenitors (CWPs) remains virtually unknown, despite its relevance to develop microbiome‐oriented tools in sustainable agriculture. Here, we quantified the rhizosphere influence—a comparison between rhizosphere and bulk soil samples—on bacterial, fungal, protists and invertebrate communities and on soil multifunctionality across nine CWPs at their sites of origin. Overall, rhizosphere influence was higher for abundant taxa across the four microbial groups and had a positive influence on rhizosphere soil organic C and nutrient contents compared to bulk soils. The rhizosphere influence on abundant soil microbiomes was more important for soil multifunctionality than rare taxa and environmental conditions. Our results are a starting point towards the use of CWPs for rhizosphere engineering in modern crops.

An MDS-based unifying approach to time series K-means clustering: application in the dynamic time warping framework - J. Fernando Vera; José M. Angulo (Stochastic Environmental Research and Risk Assessment, 2023)
Partitioning algorithms, and in particular K-means clustering, are widely used in time series analysis. K-means clustering is intrinsically related to the use of the Euclidean distance as a measure of dissimilarity. When other dissimilarity measures, such as dynamic time warping, are involved, K-means clustering is usually replaced by the optimisation of a sums-of-the-stars clustering criterion, giving rise to an algorithm other than that of K-means, such as K-medoids. Another common restriction in the implementation of K-means concerns the need to estimate the average as the cluster prototype, which may represent a drawback for this method in time series when elastic measures such as dynamic time warping are used. In this paper, we propose a multidimensional scaling based K-means clustering algorithm that enables the use of K-means clustering together with any dissimilarity measure, and in particular with dynamic time warping, without requiring us to estimate cluster prototypes for the time series. This procedure is a true K-means clustering algorithm that searches for the partition in an equivalent auxiliary configuration, usually in a dimension lower than the time series length. The approach proposed is of particular interest when dynamic time warping is used in the analysis of series of unequal length and/or when some data are missing, and hence Euclidean distances cannot be used. The performance of our procedure is tested by conducting an extensive Monte Carlo experiment, comparing the results with those obtained by K-medoids. The procedure is also illustrated with the analysis of carbon dioxide emissions from 133 countries.

Highly Pathogenic Avian Influenza (HPAI) strongly impacts wild birds in Peru - Víctor Gamarra-Toledo; Pablo I. Plaza; Fernando Angulo; Roberto Gutiérrez; Oscar García-Tello; Patricia Saravia-Guevara; Fernando Mejía-Vargas; Mirbel Epiquién-Rivera; Gonzalo Quiroz-Jiménez; Paola Martinez; Deyvis Huamán-Mendoza; Giancarlo Inga-Díaz; et al. (Biological Conservation, 2023)

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

Evaluation of long‐term changes in precipitation over Bolivia based on observations and Coupled Model Intercomparison Project models - Sergio M. Vicente‐Serrano; Oswaldo Maillard; Dhais Peña‐Angulo; Fernando Domínguez‐Castro; Iván Noguera; Jorge Lorenzo‐Lacruz; César Azorin‐Molina; Carmelo Juez; José Antonio Guijarro; Amar Halifa‐Marín; Ahmed El Kenawy (International Journal of Climatology, 2023)
Using observations and model simulations from the 5th and 6th phases of the Coupled Model Intercomparison Project (CMIP5 and CMIP6, respectively), this study evaluated changes in monthly, seasonal, and annual precipitation over Bolivia from 1950 to 2019. Results demonstrate that observed precipitation is characterized by strong interannual and decadal variability. However, long‐term precipitation trends were not identified on the annual scale. Similarly, changes in seasonal precipitation were almost nonsignificant ( p > .05) for the study period. Spatially, albeit with its complex orography, no substantial regional variations in observed precipitation trends can be identified across Bolivia. In contrast, long‐term precipitation trends, based on CMIP5 and CMIP6 models, suggest a dominance of negative trends, mainly during austral winter (JJA) (−10%) and spring (SON) (−15%). These negative trends were more pronounced in the lowlands of Bolivia (−20%). Overall, these contradictory results highlight the need for validating precipitation trend outputs from model simulations, especially in areas of complex topography like Bolivia.

Cross-sectoral impacts of the 2018–2019 Central European drought and climate resilience in the German part of the Elbe River basin - Tobias Conradt; Henry Engelhardt; Christoph Menz; Sergio M. Vicente-Serrano; Begoña Alvarez Farizo; Dhais Peña-Angulo; Fernando Domínguez-Castro; Lars Eklundh; Hongxiao Jin; Boris Boincean; Conor Murphy; J. Ignacio López-Moreno (Regional Environmental Change, 2023)
The 2018–2019 Central European drought was probably the most extreme in Germany since the early sixteenth century. We assess the multiple consequences of the drought for natural systems, the economy and human health in the German part of the Elbe River basin, an area of 97,175 km 2 including the cities of Berlin and Hamburg and contributing about 18% to the German GDP. We employ meteorological, hydrological and socio-economic data to build a comprehensive picture of the drought severity, its multiple effects and cross-sectoral consequences in the basin. Time series of different drought indices illustrate the severity of the 2018–2019 drought and how it progressed from meteorological water deficits via soil water depletion towards low groundwater levels and river runoff, and losses in vegetation productivity. The event resulted in severe production losses in agriculture (minus 20–40% for staple crops) and forestry (especially through forced logging of damaged wood: 25.1 million tons in 2018–2020 compared to only 3.4 million tons in 2015–2017), while other economic sectors remained largely unaffected. However, there is no guarantee that this socio-economic stability will be sustained in future drought events; this is discussed in the light of 2022, another dry year holding the potential for a compound crisis. Given the increased probability for more intense and long-lasting droughts in most parts of Europe, this example of actual cross-sectoral drought impacts will be relevant for drought awareness and preparation planning in other regions.

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Water table depth modulates productivity and biomass across Amazonian forests - Thaiane R. Sousa; Juliana Schietti; Igor O. Ribeiro; Thaise Emílio; Rafael Herrera Fernández; Hans ter Steege; Carolina V. Castilho; Adriane Esquivel‐Muelbert; Timothy Baker; Aline Pontes‐Lopes; Camila V. J. Silva; Juliana M. Silveira; et al. (Global Ecology and Biogeography, 2022)
Aim Water availability is the major driver of tropical forest structure and dynamics. Most research has focused on the impacts of climatic water availability, whereas remarkably little is known about the influence of water table depth and excess soil water on forest processes. Nevertheless, given that plants take up water from the soil, the impacts of climatic water supply on plants are likely to be modulated by soil water conditions. Location Lowland Amazonian forests. Time period 1971–2019. Methods We used 344 long‐term inventory plots distributed across Amazonia to analyse the effects of long‐term climatic and edaphic water supply on forest functioning. We modelled forest structure and dynamics as a function of climatic, soil‐water and edaphic properties. Results Water supplied by both precipitation and groundwater affects forest structure and dynamics, but in different ways. Forests with a shallow water table (depth Main conclusions We show that the two extremes of water availability (excess and deficit) both reduce productivity in Amazon upland ( terra‐firme ) forests. Biomass and productivity across Amazonia respond not simply to regional climate, but rather to its interaction with water table conditions, exhibiting high local differentiation. Our study disentangles the relative contribution of those factors, helping to improve understanding of the functioning of tropical ecosystems and how they are likely to respond to climate change.

Association between telomere length, frailty and death in older adults - Mariam El Assar; Javier Angulo; José A. Carnicero; Stefan Walter; Francisco J. García-García; Fernando Rodríguez-Artalejo; Leocadio Rodríguez-Mañas (GeroScience, 2021)

Long‐term variability and trends in meteorological droughts in Western Europe (1851–2018) - Sergio M. Vicente‐Serrano; Fernando Domínguez‐Castro; Conor Murphy; Jamie Hannaford; Fergus Reig; Dhais Peña‐Angulo; Yves Tramblay; Ricardo M. Trigo; Neil Mac Donald; M. Yolanda Luna; Mark Mc Carthy; Gerard Van der Schrier; et al. (International Journal of Climatology, 2021)
We analysed long‐term variability and trends in meteorological droughts across Western Europe using the Standardized Precipitation Index (SPI). Precipitation data from 199 stations spanning the period 1851–2018 were employed, following homogenisation, to derive SPI‐3 and SPI‐12 series for each station, together with indices on drought duration and severity. Results reveal a general absence of statistically significant long‐term trends in the study domain, with the exception of significant trends at some stations, generally covering short periods. The largest decreasing trends in SPI‐3 (i.e., increasing drought conditions) were found for summer in the British and Irish Isles. In general, drought episodes experienced in the last two or three decades have precedents during the last 170·years, emphasizing the importance of long records for assessing change. The main characteristic of drought variability in Western Europe is its strong spatial diversity, with regions exhibiting a homogeneous temporal evolution. Notably, the temporal variability of drought in Western Europe is more dominant than long‐term trends. This suggests that long‐term drought trends cannot be confirmed in Western Europe using precipitation records alone. This study provides a long‐term regional assessment of drought variability in Western Europe, which can contribute to better understanding of regional climate change during the past two centuries.

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Conception rate following artificial insemination with sexed semen in Holstein heifers under artificial cooling during summer compared with winter season - Abelardo Correa-Calderón; Ismael Angulo-Valenzuela; Fernando Betancourth; Francisco Oroz-Rojo; Karina Fierros-Castro; Ulises Macías-Cruz; Raúl Díaz-Molina; Leonel Avendaño-Reyes (Tropical Animal Health and Production, 2020)

Compositional response of Amazon forests to climate change - Adriane Esquivel‐Muelbert; Timothy R. Baker; Kyle G. Dexter; Simon L. Lewis; Roel J. W. Brienen; Ted R. Feldpausch; Jon Lloyd; Abel Monteagudo‐Mendoza; Luzmila Arroyo; Esteban Álvarez-Dávila; Niro Higuchi; Beatriz S. Marimon; et al. (Global Change Biology, 2019)
Most of the planet's diversity is concentrated in the tropics, which includes many regions undergoing rapid climate change. Yet, while climate‐induced biodiversity changes are widely documented elsewhere, few studies have addressed this issue for lowland tropical ecosystems. Here we investigate whether the floristic and functional composition of intact lowland Amazonian forests have been changing by evaluating records from 106 long‐term inventory plots spanning 30 years. We analyse three traits that have been hypothesized to respond to different environmental drivers (increase in moisture stress and atmospheric CO 2 concentrations): maximum tree size, biogeographic water‐deficit affiliation and wood density. Tree communities have become increasingly dominated by large‐statured taxa, but to date there has been no detectable change in mean wood density or water deficit affiliation at the community level, despite most forest plots having experienced an intensification of the dry season. However, among newly recruited trees, dry‐affiliated genera have become more abundant, while the mortality of wet‐affiliated genera has increased in those plots where the dry season has intensified most. Thus, a slow shift to a more dry‐affiliated Amazonia is underway, with changes in compositional dynamics (recruits and mortality) consistent with climate‐change drivers, but yet to significantly impact whole‐community composition. The Amazon observational record suggests that the increase in atmospheric CO 2 is driving a shift within tree communities to large‐statured species and that climate changes to date will impact forest composition, but long generation times of tropical trees mean that biodiversity change is lagging behind climate change.

Prevalence of gastrointestinal nematode infections in goat flocks on semi-arid rangelands of northeastern Mexico - Raquel Olivas-Salazar; Alfredo Estrada-Angulo; Miguel Mellado; Armando Jacinto Aguilar-Caballero; Beatriz Isabel Castro-Pérez; Eduardo Gutiérrez-Blanco; Fernando Ruiz-Zárate (Tropical Animal Health and Production, 2018)

Spatio-temporal variability of ichthyoplankton and its relationship with oceanographic conditions at the shelf break off Chilean Patagonia (43°S–51°S) - Francisca Osorio-Zúñiga; Mauricio F. Landaeta; Jorge Angulo-Aros; Fernando Balbontín (Marine Biology Research, 2018)

Stability analysis in nonstationary spatial covariance estimation - J. Fernando Vera; José M. Angulo; Juan A. Roldán (Stochastic Environmental Research and Risk Assessment, 2017)

Variation in stem mortality rates determines patterns of above‐ground biomass in A mazonian forests: implications for dynamic global vegetation models - Michelle O. Johnson; David Galbraith; Manuel Gloor; Hannes De Deurwaerder; Matthieu Guimberteau; Anja Rammig; Kirsten Thonicke; Hans Verbeeck; Celso von Randow; Abel Monteagudo; Oliver L. Phillips; Roel J. W. Brienen; et al. (Global Change Biology, 2016)
Understanding the processes that determine above‐ground biomass ( AGB ) in Amazonian forests is important for predicting the sensitivity of these ecosystems to environmental change and for designing and evaluating dynamic global vegetation models ( DGVM s). AGB is determined by inputs from woody productivity [woody net primary productivity ( NPP )] and the rate at which carbon is lost through tree mortality. Here, we test whether two direct metrics of tree mortality (the absolute rate of woody biomass loss and the rate of stem mortality) and/or woody NPP , control variation in AGB among 167 plots in intact forest across Amazonia. We then compare these relationships and the observed variation in AGB and woody NPP with the predictions of four DGVM s. The observations show that stem mortality rates, rather than absolute rates of woody biomass loss, are the most important predictor of AGB , which is consistent with the importance of stand size structure for determining spatial variation in AGB . The relationship between stem mortality rates and AGB varies among different regions of Amazonia, indicating that variation in wood density and height/diameter relationships also influences AGB . In contrast to previous findings, we find that woody NPP is not correlated with stem mortality rates and is weakly positively correlated with AGB . Across the four models, basin‐wide average AGB is similar to the mean of the observations. However, the models consistently overestimate woody NPP and poorly represent the spatial patterns of both AGB and woody NPP estimated using plot data. In marked contrast to the observations, DGVM s typically show strong positive relationships between woody NPP and AGB . Resolving these differences will require incorporating forest size structure, mechanistic models of stem mortality and variation in functional composition in DGVM s.

EPMA-World Congress 2015 - Jella-Andrea Abraham; Olga Golubnitschaja; Ildar Akhmetov; Russell J. Andrews; Leonidas Quintana; Russell J. Andrews; Babak Baban; Jun Yao Liu; Xu Qin; Tailing Wang; Mahmood S. Mozaffari; Viktoriia V. Bati; et al. (EPMA Journal, 2016)

Markedly divergent estimates of A mazon forest carbon density from ground plots and satellites - Edward T. A. Mitchard; Ted R. Feldpausch; Roel J. W. Brienen; Gabriela Lopez‐Gonzalez; Abel Monteagudo; Timothy R. Baker; Simon L. Lewis; Jon Lloyd; Carlos A. Quesada; Manuel Gloor; Hans ter Steege; Patrick Meir; et al. (Global Ecology and Biogeography, 2014)
Aim The accurate mapping of forest carbon stocks is essential for understanding the global carbon cycle, for assessing emissions from deforestation, and for rational land‐use planning. Remote sensing ( RS ) is currently the key tool for this purpose, but RS does not estimate vegetation biomass directly, and thus may miss significant spatial variations in forest structure. We test the stated accuracy of pantropical carbon maps using a large independent field dataset. Location Tropical forests of the A mazon basin. The permanent archive of the field plot data can be accessed at: http://dx.doi.org/10.5521/FORESTPLOTS.NET/2014_1 Methods Two recent pantropical RS maps of vegetation carbon are compared to a unique ground‐plot dataset, involving tree measurements in 413 large inventory plots located in nine countries. The RS maps were compared directly to field plots, and kriging of the field data was used to allow area‐based comparisons. Results The two RS carbon maps fail to capture the main gradient in Amazon forest carbon detected using 413 ground plots, from the densely wooded tall forests of the north‐east, to the light‐wooded, shorter forests of the south‐west. The differences between plots and RS maps far exceed the uncertainties given in these studies, with whole regions over‐ or under‐estimated by > 25%, whereas regional uncertainties for the maps were reported to be Main conclusions Pantropical biomass maps are widely used by governments and by projects aiming to reduce deforestation using carbon offsets, but may have significant regional biases. Carbon‐mapping techniques must be revised to account for the known ecological variation in tree wood density and allometry to create maps suitable for carbon accounting. The use of single relationships between tree canopy height and above‐ground biomass inevitably yields large, spatially correlated errors. This presents a significant challenge to both the forest conservation and remote sensing communities, because neither wood density nor species assemblages can be reliably mapped from space.

Parameters of Higuchi’s method to characterize primary waves in some seismograms from the Mexican subduction zone - Gonzalo Gálvez-Coyt; Alejandro Muñoz-Diosdado; José A. Peralta; José A. Balderas-López; Fernando Angulo-Brown (Acta Geophysica, 2012)

Simulation and properties of a non-homogeneous spring-block earthquake model with asperities - Alejandro Muñoz-Diosdado; Adolfo H. Rudolf-Navarro; Fernando Angulo-Brown (Acta Geophysica, 2012)

Effects of cumulative stressful and acute variation episodes of farm climate conditions on late embryo/early fetal loss in high producing dairy cows - Pilar Santolaria; Fernando López-Gatius; Irina García-Ispierto; Gregori Bech-Sàbat; Eduardo Angulo; Teresa Carretero; Jóse Antonio Sánchez-Nadal; Jesus Yániz (International Journal of Biometeorology, 2010)

A quantitative study of the brainstem cholinergic projections to the ventral part of the oral pontine reticular nucleus (REM sleep induction site) in the cat - Margarita Luca Rodrigo-Angulo; Elisia Rodrguez-Veiga; Fernando Reinoso-Surez (Experimental Brain Research, 2005)